The Analysis of the Book Ta'lim Muta'allim as a Etiquette Guide of Seeking Knowledge in the Digital Era - maulidah, nisa ainun; Nur Wahidah (Mu'allim, 2025)
The development of the digital era presents new challenges, the ease of obtaining information through electronic devices has shifted the way of learning. Behind this convenience, there is a decline in the application of adab values in studying, especially in maintaining ethics when studying. The purpose of this study is to analyze Kitab Ta'lim Muta'allim as a Guide to the Adab of Seeking Knowledge in the Digital Age. This article explains the adab of seeking knowledge in the ta'lim muta'allim book, the relevance of the ta'lim muta'allim book to the digital era, and the conditions of online learning in the digital era. This research uses a qualitative method with a literature study approach. Data collection is done by collecting information and data through the use of various material sources available in the library, such as documents, books, journals, historical records and others. The results showed that, things that must be considered when seeking knowledge contained in the ta'lim muta'allim book, namely, choosing / looking for the best knowledge and needed in religious life, prioritizing the science of tawhid, and prioritizing ancient knowledge or old knowledge over new knowledge.